PENGARUH MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA PADA KARYAWAN PABRIK KRUPUK PULI “TELOR WALET” DUSUN KEMBANGAN DESA GARON KECAMATAN BALEREJO KABUPATEN MADIUN - Endang Rahmawati (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2014)
This research have a purpose to study about influence of motivation work to employees productivity. Motivation represent one of factor influencing employees productivity. With existence of good motivation a employees will be responsible for the work and the work will be completed effectively and efficiently. The samples in this study using the saturated sample is all employees working in the factory pulleys crackers "Telor Walet" Madiun. In analyzing the data used product moment correlation statistical method to test the validity of the instruments used in regression testing method to test the hypothesis put forward in this study. Pursuant to result of research obtained the level of value of rcount 0.717 and rtable 0.339 table, on the other hand the level of Sighitung 0,000 and Sigprob 0,05. Matter this means that value of rcount ≥ rtable (0.717 ≥ 0.339) or Sigcount ≤ Sigprob (0,000 ≤ 0,05). While, level of R2 (R Square) 0,514. Becoming, contribution influence of motivation work to performance equal to 56,6% while the rest equal to 43,4% influenced by other factor. From result of test of F obtained the level of value of Fcount 33.830 and Ftable 4.149, on the other hand the level of Sigcount 0,000 and of Sigprob 0,05 matter this means that value of Fcount ≥ Ftable (46,973 ≥ 4,113) or Sigcount ≤ Sigprob (0,000 ≤ 0,05).In test of t can be made line of regresi the following Y= Y 10,320 + 0,773X, its meaning if motivation improved once will happened increase of employees productivity counted 0,773%, if the other factor remain to. Level of value of tcount 5.816 and ttable 2.037, on the other hand the level of Sigcount 0,000 and Sigprob 0,05, matter this means that value of tcount ≥ ttable (5.816 ≥ 2.037) or Sigcount ≤ Sigprob (0,000 ≤ 0,05). On the basis of correlation test, test F and test of t can be concluded that there is influence Motivation Work to Productivity Employees Pabrik Krupuk Puli "Telor Walet" Madiun.